The Kandha Society and Culture of Odisha - Miniaka, Santosh; Tripathy, Sishir Kumar (International Journal of Psychosocial Rehabilitation, 2020)
Odisha is the homeland of the tribal. Here we can find as many as sixty two type of tribes among them the Kandha tribe is considered to be the major tribe. They found in the Rayagada, Koraput, Kandhamal, Kalahandi and also all over the Odisha. They speak the Kui/Kuvi language which belongs to the Dravidian linguistic group. Agriculture is their main occupation. They dwell in the brick and mud house which their roof is covered with the tall grass. They eat Gruel, rice and roots of the forest. There are different types of Kandhas i.e. Desia Kandha, Dangaria Kandha, Sitha Kandha, Kandha dora, Kutia Kandha, Malua Kandha, Buda Kandha , Raj Kandha etc. Among the above the Kutia and the Dangaria are considered as the Particular Vulnerable Tribal Groups (PVTG’s).